SIKAP MEDIA MENGENAI AKSI REUNI 212 Analisis Framing Aksi Reuni 212 pada Cnnindonesia.com dan Republika.co.id - Wiwid Adiyanto (Jurnal Ilmu Komunikasi AKRAB, 2020)
Media framing might drive people’s views on an event. The so-called ‘212’ campaign in 2016 was repeated in 2018 (adopting the theme ‘reunion’ this time). This does not escape from media coverage. The purpose of the 2018 campaign is questionable. First, the use of religious claims to deliver the campaign was held approaching 2019 presidental election ; and the second is the participation of the opposing politicians. This study is aimed at examining the political views of media throughout such campaign. This research use Entman’s framing method to campare Cnnindonesia.com and Republika.co.id reports that cover this campaign. The result shows that CNN Indonesia desribes possible violations of general election’s regulations. On the other hand, Republika frames such campaign as a pure religious campaign without any voilation of such regulations.